Turbulent velocity measurements in high Reynolds cryogenic helium facilities at Service des Basses Températures (SBT). (April 2019) - Kharche, S; Moro, J P; Baudet, C; Rousset, B; Fuchs, A; Peinke, J; Girard, A
Abstract: Due to its very low viscosity, cryogenic helium has been used for years to generate high Reynolds turbulent flows. The measurement of velocity fluctuations in such high Reynolds flows is however a challenging issue, as it is necessary to develop small size (typically micron-length), robust sensors, to measure the whole spectrum of fluctuations of the velocity, which may extend to hundreds of kHz and possibly higher. SBT has developed for years different facilities, in particular taking benefit of the refrigeration capacities available at CEA Grenoble. In this article we present the current status of developments of hot wire sensors at CEA. Different characterizations of Wollaston hot wires are shown, and measurements of velocity fluctuations in different conditions, in normal helium as well as in superfluid helium are shown.